The relationship between educational capabilities and entrepreneurial performance A study on a sample of service sector establishments operating in the state of Khartoum, 2022 - Muhammad, Hassan Abdul Rahim Fadl; Muhammad, Sheikh Muhammad al-Khidr; Madkhali, Hudhayfah Hadi; Souissi, Anis Muhammad Salih (Journal of Economic, Administrative and Legal Sciences, 2023)
The importance of this study and its expected results was to analyse the relationship between educational capabilities and entrepreneurial performance in the service sector of Khartoum State.The research included answering questions related to the research problem using a descriptive method. The reliability for study purposes the questionnaire were designed to collect data from study sample in service institution of Khartoum State. The study used improbability sample and distributed 300 questionnaires returned 298 questionnaires represent of 99%. The study used (SPSS) and equation structural modelling (ESM).The most important findings revealed that there is a positive relationship between educational capabilities dimensions (managerial commitment experiment) and entrepreneurial performance dimensions (entrepreneurial indicator effectiveness).
Keywords: educational capabilities; entrepreneurial performance; entrepreneurial index; entrepreneurship; Khartoum